Algunas aves de gaitania: (municipio de ataco, tolima, colombia) (1960)
This paper is a contribution to the knowledge of the avifauna of the Upper Magdalena River in Colombia.  The birds, representative of 50 species and subespecies, were taken at Gaitania Municipio de Ataco, Tolima, a zone of humid forest on the eastern of the Central Andes (30) 8 N., 750 49' W. of Greenwich. Alt. 2100 m. approx.).